Model Pemerolehan Bahasa Arab Sebagai Bahasa Kedua (Kajian Psikolinguistik) - Tania, Elis; Agung, Setiyawan (Journal of Arabic Education and Linguistic, 2023)
This research aims to describe models and theories of second language acquisition in psycholinguistic studies. This research uses a descriptive qualitative approach, which focuses on description and data analysis to understand the phenomenon being studied in depth. The method used in this research is library research, where researchers collect data from scientific articles and books that are relevant to the research topic. The data obtained was then analyzed using content analysis techniques, namely the researcher identified themes and patterns in the data collected. The research results show several theories from language experts and linguists which describe the theory of second language acquisition developed by psychologists and linguists such as B.F. Skinner, Noam Chomsky and Stephen D Krashen. All three will provide broad insight into the concrete empirical aspects as well as the abstract intuitive aspects of second language acquisition.